Macro-Meso failure mechanisms and slip characteristics of jointed sandstone under uniaxial compression - Junguang Wang; Song Yang; Bing Liang; Tianyu Xin; Lingran Ren (Results in Engineering)
Fault sliding is one of the important causes of induced coal mine dynamic disasters during deep mining. To systematically investigate the slip behavior of fault structures under in-situ stress conditions, jointed sandstone specimens with different joint inclinations were prepared, and uniaxial compression tests of jointed sandstone and multi-scale mechanical analysis were carried out by combining acoustic emission(AE) monitoring and digital image correlation(DIC) technique. A discrete element model was developed to simulate jointed sandstone, with model validity confirmed through parametric calibration. The results show that: (1)The stress-strain response of jointed sandstone specimens exhibits a distinctive edge dislocations stage, which gradually changes into a joint slip stage with the increase of joint inclination; (2)The presence of joints significantly reduces the rock strength, altering failure modes from tensile-shear conjugate failure to shear-slip instability; (3)The larger the joint inclination, the more concentrated the crack distribution, the more energy dissipation, and the greater the slip risk. The microcrack initiation is at its earliest near the joint. (4)According to the definition of W as the ratio of dashpot energy to slip energy during loading, two failure modes of jointed sandstone are given, namely “Slip + Crack propagation dominant type” and “Crack propagation + Slip dominant type”. The research results can provide a reference for the prevention and control of coal mine dynamic disasters induced by fault activation.